External risks variable associated with success in construction (Gaceta Técnica, 2024)
This study presents a quantitative methodology to evaluate the negative impact of External Risks on the productivity of civil and industrial works in the country, considering the uncertain nature of these factors. The methodology identifies, analyzes and evaluates various risks at an international, national, regional and local level, estimating their probability of occurrence and their potential impact on project productivity. Mathematical formulations are proposed to calculate efficiency, progress and execution times, based on uncertain data, the maximum speed of labor consumption and the lost man-hours associated with risks. The application in project management is proposed, allowing management to anticipate future scenarios, optimize the allocation of resources and improve communication with interested parties. The methodology presented here also aims to lay the foundations for national regulations that consider the impact of these risks and their costs, facilitating the agreement between client and contractor
Keywords: S curve; external risks in construction; construction project management; The Pitia; expertise; organizational vulnerability